Кинетика процесса электроэкстракции никеля из промышленных сливов алмазного производства - Богатырева, Г.П.; Маринич, М.А.; Базалий, Г.А.; Олейник, Н.А.; Зайцева, И.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Processes of electrochemical metal extraction from industrial solutions of diamond manufacture are an integral part complex resource saving technology of extraction of synthetics diamond products. The purpose of the present work was the establishment of kinetics laws of process of electrochemical extraction of nickel from industrial solutions. It is established that speed of electrochemical extraction of nickel is influenced by many factors: concentration of ions of metals in a solution, a material of the cathode, temperature of solution, stirring, density of a current. It is shown that the working density of a current is 500—1000 А/m², optimum temperature is 65—70 °С, the time of electrochemical extraction of nickel is 20—30 h.